Peripheral blood basophils are the main source for early interleukin-4 secretion upon in vitro stimulation with Culicoides allergen in allergic horses. - Fahad Raza (Public Library of Science (PLoS), 2021)
Interleukin-4 (IL-4) is a key cytokine secreted by type 2 T helper (Th2) cells that orchestrates immune responses during allergic reactions. Human and mouse studies additionally suggest that basophils have a unique role in the regulation of allergic diseases by providing initial IL-4 to drive T cell development towards the Th2 phenotype. Equine Culicoides hypersensitivity (CH) is a seasonal immunoglobulin E (IgE)-mediated allergic dermatitis in horses in response to salivary allergens from Culicoides (Cul) midges. Here, we analyzed IL-4 production in peripheral blood mononuclear cells (PBMC) of CH affected (n = 8) and healthy horses (n = 8) living together in an environment with natural Cul exposure. During Cul exposure when allergic horses had clinical allergy, IL-4 secretion from PBMC after stimulation with Cul extract was similar between healthy and CH affected horses. In contrast, allergic horses had higher IL-4 secretion from PBMC than healthy horses during months without allergen exposure. In addition, allergic horses had increased percentages of IL-4+ cells after Cul stimulation compared to healthy horses, while both groups had similar percentages of IL-4+ cells following IgE crosslinking. The IL-4+ cells were subsequently characterized using different cell surface markers as basophils, while very few allergen-specific CD4+ cells were detected in PBMC after Cul extract stimulation. Similarly, IgE crosslinking by anti-IgE triggered basophils to produce IL-4 in all horses. PMA/ionomycin consistently induced high percentages of IL-4+ Th2 cells in both groups confirming that T cells of all horses studied were capable of IL-4 production. In conclusion, peripheral blood basophils produced high amounts of IL-4 in allergic horses after stimulation with Cul allergens, and allergic horses also maintained higher basophil percentages throughout the year than healthy horses. These new findings suggest that peripheral blood basophils may play a yet underestimated role in innate IL-4 production upon allergen activation in horses with CH. Basophil-derived IL-4 might be a crucial early signal for immune induction, modulating of immune responses towards Th2 immunity and IgE production.